Leadership and power : identity processes in groups and organizations - Knippenberg, Daan van, 1966-; Hogg, Michael A., 1954- (SAGE, 2003)
Leadership and associated power issues lie at the core of group life in a variety of contexts. Even the most informal of groups typically have some form of leadership in their organization, and the understanding of leadership and power from a psychological standpoint can inform a greater understanding of group dynamics both inside and outside of the workplace.
Keywords: Leadership.; Power (Social sciences); Group identity.; Intergroup relations.; Organizational behavior.; Pouvoir (Sciences sociales); Identité collective.; Relations intergroupes.; Comportement organisationnel.; group identity.; POLITICAL SCIENCE -- Political Process -- Leadership.; Organizational behavior; Intergroup relations; Group identity; Leadership; Organisation; Identität; Sozialpsychologie; Führung; Macht; Leiderschap.; Aufsatzsammlung.